Komitmen pada Panggilan Kristus: Integrasi Filipi 3:13-14 dengan Goal Commitment Theory - Sherly Mudak; Debora Inda Violita Praing (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
This research discusses the commitment of God's servant based on Philippians 3:13-14 and its integration with Goal Commitment Theory. The background of the problem shows that God's servants often face challenges in maintaining commitment to divine calling in the midst of complex ministry dynamics. The purpose of this research is to explore the relevance and application of the principles of commitment in a spiritual context, as well as how theory can strengthen the dedication of God's servants. This study uses a qualitative approach with hermeneutic analysis of the text of Philippians 3:13-14 and a literature review on Goal Commitment Theory. The results show that a strong commitment to divine purpose can increase motivation and effectiveness of ministry, where community support and self-reflection are key factors. The conclusion of this study confirms that the integration between biblical principles and modern theories provides a strong foundation for God's servants to stay focused and dedicated in carrying out their calling.